JAZ8 Interacts With VirE3 Attenuating Agrobacterium Mediated Root Tumorigenesis - Li, Shijuan; Xu, Bingliang; Niu, Xiaolei; Lu, Xiang; Cheng, Jianping; Zhou, Meiliang; Hooykaas, Paul J. J. (Frontiers in Plant Science, 2021)
Agrobacterium tumefaciens can cause crown gall tumors by transferring both an oncogenic piece of DNA (T-DNA) and several effector proteins into a wide range of host plants. The translocated effector VirE3 was reported to bind to the Arabidopsis thaliana pBrp protein to activate the expression of VBF, an F-box protein involved in degradation of the VirE2 and VIP1 proteins, facilitating Agrobacterium transformation (AMT). Although some molecular functions have been elucidated, the roles of VirE3 participate in virulence still need to be further investigated. Here, we identified that AtJAZ8 interacted with VirE3 in a yeast two hybrid screening assay and the interaction was confirmed by pull-down and BiFC assay. We also found deletion of virE3 reduced Agrobacterium virulence and overexpression of virE3 in Arabidopsis enhances Agrobacterium virulence in root tumor assay. Interesting, overexpression of JAZ8 in Arabidopsis significantly decreased Agrobacterium infectivity. Further experiments demonstrated AtJAZ8 inhibited the activity of VirE3 as a plant transcriptional regulator and overexpression of AtJAZ8 in Arabidopsis activated AtPR1 gene expression while repressed the expression of AtPDF1.2. Conversely, overexpression of virE3 in Arabidopsis suppressed the expression of AtPR1 whereas activated the expression of AtPDF1.2. Our results proposed a novel mechanism of counter defense signaling pathways used by Agrobacterium, suggesting that VirE3 and JAZ8 may antagonistic modulate the SA/JA mediated plant defense signaling response during Agrobacterium infection.